The Role of Informed Consent Against Doctor's Legal Protection in Health Services - Kasiman, Kasiman; Azhari, Aidul Fitricia; Rizka, Rizka (Universitas Katolik Soegijapranata Semarang, 2023)
The urgency of Informed Consent is really needed by doctors to be used as a sign of approval for medical action that has the potential for medical disputes or is a legal protection for medical officers who carry out actions. The purpose of this study was to analyze informed consent for the legal protection of doctors in health services. Using a normative juridical method with a statute approach, namely examining all laws and regulations related to the issues to be discussed. The results of the analysis show that absolute informed consent can be a guarantee of a sense of security for both doctors and workers who carry out the health care profession as well as protection for patients so that patients understand the condition of the disease experienced by patients and understand the medical actions that will be carried out so as to avoid malpractice activities.